Epidemiological and Clinical Aspect of Scorpion Stings in the Region of Azilal - enourhbi, Abdellah; auhmani, anas; Quamous, Youssef (International Journal of Innovative Research in Medical Science, 2024)
Conducted over two years (2020-2021), study included hospitalized patients with scorpion stings, totaling 210 cases admitted to the Provincial Hospital of HAUT ATLAS AZILAL. Patients, with a mean age of 11.4 years, showed a female predominance. Most cases (73.81%) were from rural areas, with 67.14% of bites occurring at night and primarily affecting distal limb parts (91%). Summer months, especially July, August, and September, saw a peak in frequency (70.4%). Black scorpions accounted for 61.9% of stings. The post-sting time varied from 30 to 370 minutes, with 63.8% treated before the second hour. Clinically, 36% were in class I (Local Signs), 51% in class II (General Signs), and only 13% in class III (Vital Distress).